ANALISIS IMPLEMENTASI KEBIJAKAN KUOTA JEMAAH HAJI PASCA PERPINDAHAN KEMENTERIAN AGAMA KE KEMENTERIAN HAJI DAN UMRAH - Rifa Fahrijal (CV. Adiba Aisha Amira, 2026)
Changes in the governance of Hajj management through the establishment of the Ministry of Hajj and Umrah represent part of the Indonesian government’s bureaucratic reform aimed at improving the quality of religious public services. This study aims to analyze the implementation of Hajj quota policy following the transfer of authority from the Ministry of Religious Affairs to the Ministry of Hajj and Umrah. The research employs a library research method with a qualitative descriptive approach. Data were obtained through literature studies, including scientific journals, regulations, government documents, and academic articles related to Hajj management in Indonesia. The findings indicate that institutional reform has brought positive impacts, such as improved service professionalism, greater transparency in quota distribution, digitalization of administrative systems, and strengthened bureaucratic coordination. However, the implementation of the policy still faces various challenges, including quota limitations set by the Government of Saudi Arabia, bureaucratic transition issues, weak oversight mechanisms, and the potential for abuse of authority in quota distribution. The study concludes that institutional reform is a strategic step in improving Hajj governance; however, its success largely depends on effective supervision, digital system integration, and consistent application of good governance principles.